Factors that Promote and Inhibit Career Progression for Maritime Professionals - Saveikienė, Diana (Jaunųjų mokslininkų darbai, 2016)
The maritime labour market is characterized by extreme changes in the workplace and legal regulations. This urges to carry out research in career progression for maritime professionals. The aim of this research was to identify the factors that have influence on career progression. for maritime professionals. Practical considerations of this research are related to competency framework for professionals within the marine industry.Profession choices and the career concept have been analysed in the theoretical section of the paper. Quantitative and qualitative research and expert surveys were carried out in order to identify factors that promote/inhibit career progression for maritime professionals. The findings are provided in the empirical section. Literature review showed that jobs within the marine industry are well-paid, seafarers are encouraged to take part in public life, develop spiritual values, their needs and expectations are met. Research showed that the majority of the respondents choose a seafarer’s profession because of such subjective factors as interests, hobbies, personality traits, meanwhile objective factors are less important. The majority of the respondents, especially the younger ones, in both marine navigation and engineering, expect to achieve a higher rank. The main factors that inhibit their career progression are responsibility and job strain. Analysis showed that subjective and objective factors that promote/inhibit career progression within the marine industry develop at a younger age. If mariners fail to achieve a higher rank at a younger age, subjective career progression inhibiting factors develop. Thus, career progression prospects are very important, especially at a younger age. The obtained data show that an additional factor may develop in  young seafarers – they may decide to leave the profession.
Keywords: maritime professionals; profession; career; career within the marine industry; career framework